Jatropha sotoi-nunyezii and Jatropha curcas, species from Tamaulipas: a comparison from a biofuels perspective - Guevara-Fefer, Patricia (Universidad Autónoma de Tamaulipas, 2016)
Species of the genus Jatropha are considered a viable alternative for commercial production of biodiesel, particularly J. curcas. Recently J. sotoinunyezii species was described, with distribution in Tamaulipas state, but the feasibility for its industrial use remains unknown. The objective of this work was to characterze the quality and yield of the biodiesel obtained from J. sotoinunyezii as compared with the toxic and nontoxic commercial varieties of J. curcas. The oil from both toxic and non-toxic J. curcas as well as J. sotoi-nunye-zii seeds was transesterified to produce biodiesel and its chemical composition (fatty acid methyl esters) by GC-MS was determined. The seeds from J. sotoi-nunyezii had a higher oil yield than those from the toxic and non-toxic J. curcas varieties (43.5 %, 32.5 % and 33.3 % respectively). The biodiesel conversion efficiency was higher in J. sotoi-nunyezii with 87.2 %. The biodiesel obtained from J. sotoi-nunyezii showed a higher amount of insaturated methyl esters, particularly methyl linoleate. This feature influenced the calculated values of iodine value and cetane number that compared with quality standards such as EN 14214, indicate that the J. sotoi- nunyezii biodiesel is more susceptible to oxidation with respect to that of toxic and non-toxic J. curcas. On the other hand, the calcul ted heating value of biodiesel from J. sotoi-nunyezii and toxic and non-toxic J. curcas is similar to that of diesel.